Existence of positive solutions for a class of second-order discrete problems with p-Laplace operators(一类带p-Laplace算子的二阶离散问题正解的存在性) - 仲海林(ZHONG Hailin); 高承华(GAO Chenghua) (Zhejiang Daxue xuebao. Lixue ban, 2025)
We obtain the existence and multiplicity of positive solutions for a class of second-order discrete p-Laplace problems with Dirichlet boundary conditions by using the upper and lower solution method; The obtained results are then extended to the corresponding second-order discrete p-Laplace systems.运用上下解方法证明了一类带Dirichlet边界条件的二阶离散p-Laplace问题正解的存在性和多解性；并将所得结果推广至相应的二阶离散p-Laplace系统。